Adaptation to a Sibling Culture: The Satisfaction and Persistence Intentions of Mainland Chinese Postgraduate Students at a Hong Kong University - Min Zeng; David Watkins (UiTM Publisher, 2007)
This study proposed and tested a model of the adaptation of postgraduate students to a "sibling culture", namely, Mainland Chinese students at the University of Hong Kong. The model was based on higher education literature combined with acculturation elements for the construct of social integration. Students' satisfaction with their experience in this cultural setting and the likelihood of their persistence were used as the indicators of their adaptation in a model linking various background variables such as academic and social integration to adaptation. The participants were 103 current research students. Analysis showed that academic integration was more strongly related than social integration to their satisfaction and likely persistence in post-graduate study at this university. Among the background variables measured, motivation and Cantonese but not English language skills showed a significant relationship with postgraduate students' academic and social integration. Implications for research on and assistance to mainland postgraduate students in Hong Kong are discussed.